Factors Affecting Patient Satisfaction and Patient Loyalty in Hospitals: Systematic Literature Review - Parmana, Anang Dwi; Paramarta, Vip; Nurina, Yafanita Izzati (UNUSA Press, 2024)
Introduction: In response to the demand for high-quality services, healthcare providers are faced with an increasing number of hospitals in Indonesia, which encourages competition to offer these services. Patient satisfaction, influenced by their expectations and experiences of the services received, is a key indicator in evaluating service quality. Additionally, patient loyalty is established through their trust in the hospital and contributes to the sustainability of healthcare services. Objective: This literature review aims to identify factors that play a role in influencing patient loyalty and satisfaction. Methods: The inclusion criteria are articles published between 2020 and 2024, research conducted in hospitals, with open access and full text. The article selection process resulted in seven articles that will be examined further. Results: Service quality (tangible, reliability, responsiveness, assurance, and empathy), trust, and hospital image have a positive influence on patient satisfaction and loyalty. Furthermore, patient satisfaction plays a crucial role in directly reinforcing patient loyalty. Therefore, improving service quality and establishing a good hospital image is essential not only to satisfy patients but also to ensure the sustainability and competitiveness of the hospital amid increasingly fierce competition in healthcare service provision. Conclusions: The findings of this study indicate that hospital image and service quality have a positive influence on patient loyalty and satisfaction.